PENGARUH PEMBERIAN EDUKASI GIZI OLAHRAGA TERHADAP PENGETAHUAN DAN POLA KONSUMSI ATLET KARATE - Boby Gultom; Rodrigo Situmorang; Joko Wantri Lumbantoruan; Kornelius Agata Manurung; Ade Setiowati (STKIP Subang, 2026)
Abstract Objective. This study aimed to evaluate the effectiveness of a systematically designed sports nutrition education program in enhancing nutritional knowledge and improving dietary patterns among adolescent karate athletes actively competing in the Medan area. This initiative was grounded in the understanding that karate, as a high-intensity martial art, demands optimal physiological and mental readiness—attributes that cannot be achieved without adequate and well-planned nutritional support. Methods. A quasi-experimental design with a pretest-posttest control group approach was employed. The study involved 40 adolescent karate athletes (aged 15–18 years) divided into two groups: an intervention group that participated in a structured sports nutrition education program (weekly 90-minute sessions over four weeks) and a control group that continued regular training without exposure to any nutrition education materials. Variables were measured before and after the intervention using a validated 30-item multiple-choice sports nutrition knowledge questionnaire and a modified semi-quantitative Food Frequency Questionnaire (FFQ) to assess the athletes' daily dietary patterns. Results. Analysis of Covariance (ANCOVA) results, using pretest scores as a covariate, revealed a highly statistically significant difference in nutrition knowledge scores between groups following the intervention (F(1,37) = 45.32, p < .001), accompanied by large effect sizes according to Cohen’s criteria (η²p = .55; Cohen’s d = 1.95). Similarly, the consumption pattern variable showed a significant between-group difference (F(1,37) = 38.76, p < .001) with equally large effect sizes (η²p = .50; Cohen’s d = 1.80). Collectively, these results indicate that the sports nutrition education program delivered had an impact that was not only statistically significant but also practically meaningful regarding the enhancement of nutritional competence among adolescent karate athletes. Conclusion. A structured